Implementation Of Affordable Housing (Rmb) Through Waqf Instrumentation - Sukamto, Fifi Anti Mapika Sari; Haji Hashim, Hydzulkifli; Osman, Amirul Faiz (Advanced Scientific Research, 2021)
Housing is one of the most important and crucial sectors in ensuring the well-being and growth development of the country. Housing needs should be categorized in the Daruriyyah Maqasid Al Shariah hierarchy. In the context of Hifz An-Nafs collectively carries the meaning of how important it is to meet the basic needs of a human being as a survival. Therefore, with the population of Johor increases to 3.7 million people by 2020, the issue of insufficient housing should be provided properly to ensure that every segment of society can afford to own a house, especially for the B40 and M40 respectively. The study aims to discuss four important aspects, namely on the insufficiency of affordable housing in Johor, the extent of implementation of affordable housing in Johor, identify methods of affordable housing using waqf instrumentation, and the last to provide affordable housing models using waqf instruments in Johor. This is carried out by using the methodology of qualitative method of interviewing expert interview where the parties interviewed are the parties who have been involved in the development of waqf property and the party who manages waqf property. To support the statements given by experts, document analysis methodology is also used. Meanwhile, the proposed model of waqf instrumentation development was obtained after the analysis was done. Through this study, it is hoped to be able to help stakeholders such as the government, Johor Islamic Religious Council, developers, and researchers to better understand the problems present in the development of waqf land to develop affordable housing. The results of this study are expected to benefit the parties concerned in compensating for the insufficiency of affordable housing as well as making Johor emulate the concept of Baldatun Toyibbah wa Robbun Ghofur